2015
DOI: 10.1177/0092055x15619217
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning as a Potentially Winning Combination of Face-to-face and Online Learning

Abstract: Blended learning, in the form of screencasts to be viewed online outside of class, was incorporated into three sections of an introductory sociology course in a liberal arts college setting. The screencasts were used to introduce concepts and theories to provide more time for discussion in class and more opportunity for students to review concepts and theories outside of class. Students' use and their perceptions of the impact of the screencasts were assessed with an in-class survey instrument in addition to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 10 publications
4
53
0
6
Order By: Relevance
“…NMC Horizon Report: 2017 Higher Education Edition states blended Learning is a significent technology to promote higher education in the next 1~2 years [3]. Domestic and foreign research show that blended learning is more and more used in different levels and different subjects teaching [4][5]. In terms of implementation for blended learning, most research are with the help of online learning, such as E-learning, M-learning, WeChat learning, MOOC (Massive Open Online Courses) and ICT (information and communication technology).…”
Section: A Blended Learningmentioning
confidence: 99%
“…NMC Horizon Report: 2017 Higher Education Edition states blended Learning is a significent technology to promote higher education in the next 1~2 years [3]. Domestic and foreign research show that blended learning is more and more used in different levels and different subjects teaching [4][5]. In terms of implementation for blended learning, most research are with the help of online learning, such as E-learning, M-learning, WeChat learning, MOOC (Massive Open Online Courses) and ICT (information and communication technology).…”
Section: A Blended Learningmentioning
confidence: 99%
“…Bu sebeple bazı eğitim kurumları yüz yüze etkileşimin sağlandığı geleneksel sınıf ortamında teknolojik materyalleri tercih ederken bazıları ise çevrim içi teknolojiler aracılığıyla hedeflenen eğitsel içeriği öğretmeyi amaçlamaktadırlar. Bu nedenle her iki yönteminde içerisinde yer aldığı karma (blended, hybrid, mixed) öğrenme ortamları tasarlanmaktadır (Auster, 2016).…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Two-thirds of all universities and colleges in the United States offer hybrid or online courses [3]. Hybrid courses incorporate blending learning in that the courses make use of both face-to-face and online learning [4]. Some academics have suggested that hybrid learning may be the best of both worlds and deliver the "optimal mix" of online and traditional learning.…”
Section: Introductionmentioning
confidence: 99%
“…By meeting with students throughout the semester instructors in hybrid courses are able to informally gage learning, create collaborative learning environments, motivate students, answer questions about course requirements, and engage in spontaneous an unstructured discussion with students. The addition of an asynchronous online component offers the capacity for instructors to offer independent, flexible, convenient, accessible studentcentered learning, an improved ability to analyze and assess learning and provide immediate feedback on quizzes and exams, the opportunity for participation in discussion by students who are uncomfortable participating in the public setting of the classroom, and consistent access for students to course materials [1], [4], [5], [6], [7], [8]. Moreover, in hybrid courses a considerable amount of "course housekeeping" can be done online.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation